PELIBATAN ORANG TUA DALAM PENINGKATAN KEMAMPUAN BERCERITA ANAK TK MELALUI LITERASI DIGITAL - Lina Kamalia Zahra; Lina Putriyanti (STKIP Subang, 2024)
The aim of this research is to determine the effect of parental involvement in improving children's storytelling abilities through the introduction of digital literacy. This research method uses descriptive qualitative procedures. The research subjects were 10 kindergarten children. Data collection techniques were through observation and interviews with 2 teachers at Aisyiyah Bustanul Athfal Jatimulyo Kindergarten and 10 parents. Based on data analysis, it shows that out of 10 parents, 3 of them accompany their children in using digital literacy, the other 6 only let their children play with their own devices. Based on observations made by 2 teachers with 10 children, it shows that children who receive assistance in using digital literacy show Their ability to tell stories is higher than children who do not receive assistance from their parents. The research results show that parental involvement in the use of digital literacy can improve children's storytelling abilities.